2004
DOI: 10.1128/jvi.78.3.1464-1472.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Polo-Like Kinase Pathway in CD4 + T Cells Is Characteristic of Pathogenic Simian Immunodeficiency Virus Infection

Abstract: CD4؉ T-cell dysfunction highlighted by defects within the intracellular signaling cascade and cell cycle has long been characterized as a direct and/or indirect consequence of human immunodeficiency virus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…rhesus macaques) and nonpathogenic (i.e., SMs) SIV infection has shown that a variety of cell cycle perturbations is observed in apoptosis-sensitive T cells derived from the peripheral blood and lymph nodes of macaques infected with SIV and progressing to AIDS, while normal cell cycle regulation is observed in apoptosis-resistant T cells from naturally SIVinfected SMs that do not progress to AIDS. 128 Taken together, these findings suggest that during pathogenic HIV and SIV infections (but not during nonpathogenic SIV infection of natural hosts), the presence of cell cycle dysregulation is involved in determining the abnormal susceptibility to apoptosis of T lymphocytes. 124 The Interaction between the Envelope Glycoprotein and CD4/coreceptors is a Crucial Factor in the Pathogenesis of AIDS HIV-1 infection can cause apoptosis via a variety of mechanisms, some of which rely directly on the intricate interaction between the virus and the host cells, and some of which act indirectly through activation of the host's inflammatory reaction and immune system activation.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 79%
“…rhesus macaques) and nonpathogenic (i.e., SMs) SIV infection has shown that a variety of cell cycle perturbations is observed in apoptosis-sensitive T cells derived from the peripheral blood and lymph nodes of macaques infected with SIV and progressing to AIDS, while normal cell cycle regulation is observed in apoptosis-resistant T cells from naturally SIVinfected SMs that do not progress to AIDS. 128 Taken together, these findings suggest that during pathogenic HIV and SIV infections (but not during nonpathogenic SIV infection of natural hosts), the presence of cell cycle dysregulation is involved in determining the abnormal susceptibility to apoptosis of T lymphocytes. 124 The Interaction between the Envelope Glycoprotein and CD4/coreceptors is a Crucial Factor in the Pathogenesis of AIDS HIV-1 infection can cause apoptosis via a variety of mechanisms, some of which rely directly on the intricate interaction between the virus and the host cells, and some of which act indirectly through activation of the host's inflammatory reaction and immune system activation.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 79%
“…Total RNA was extracted with TRIZOL (Invitrogen) and real-time PCR was performed with MyiQ Single-Color Real-Time PCR Detection System (Bio-Rad) as described [37]. Briefly, cDNA samples were subjected to real-time PCR in an iCycler (Bio-Rad) and SYBR Green fluorescence quantification (PE Applied Biosystems; Foster City, CA, USA).…”
Section: Real Time-polymerase Chain Reaction (Real Time-pcr)mentioning
confidence: 99%
“…Our laboratory has been involved with studies of the mechanisms of pathogenesis of lentivirus infection using the simian immunodeficiency virus (SIV) infected non-human primate model (2527). We and others have shown that, similar to HIV infection in humans, there are phenotypic changes and functional impairment in the NK cell population that occur during both acute and chronic phases of SIV infection in rhesus macaques (RMs) (28, 29).…”
mentioning
confidence: 99%